Deletion of the PPARδ gene exacerbates high-fat diet-induced nonalcoholic fatty liver disease in mice through the gut-liver axis: PPAR δ deletion induced fatty liver disease in mice - Wang, Ya-tao; Wang, Feng-fan; Li, Hong; Xu, Jing-yuan; Lu, Xiao-lan; Wang, Yan (Cellular and Molecular Biology, 2023)
Gut microbiota dysbiosis is an essential factor contributing to non-alcoholic fatty liver disease (NAFLD), in which the gut-liver axis plays a crucial role. Peroxisome proliferator-activated receptor δ (PPARδ) is considered a new direction for the research on NAFLD due to its positive regulation of glucose and lipid metabolism. Our experiment aimed to investigate the effect of PPARδ gene deletion on gut microbiota and NAFLD through the gut-liver axis. PPARδ-/- mice and wild-type mice were randomly divided into high-fat diet(HFD) groups and normal diet groups. In each group, six mice were sacrificed at weeks 4, 8, and 12. Metabolic indicators and inflammation indicators were measured, and the degree of liver steatosis and the ileum mucosa integrity were evaluated. Additionally, fecal samples were subjected to 16S rDNA gene sequencing and analysis of gut microbiota. Deletion of the PPARδ gene exhibited exacerbated effects on HFD-induced NAFLD and displayed more severe liver inflammation and intestinal mucosal barrier injuries. The HFD reduced the abundance of short-chain fatty acid (SCFA)-producing bacteria and increased the abundance of intestinal endotoxin-rich bacteria in mice. Deletion of the PPARδ gene exacerbated this trend, resulting in decreased abundances of norank_f__Eubacterium_coprostanoligenes_group and Alloprevotella and increased abundances of Acidibacter, unclassified_f__Comamonadaceae, unclassified_c__Alphaproteobacteria, unclassified_f__Beijerinckiaceae, unclassified_f__Caulobacteraceae, unclassified_c__Bacteroidia and Bosea. Spearman’s correlation analysis found Lachnoclostridium, unclassified_f__Rhizobiaceae, Allobaculum, Acinetobacter, Romboutsia, norank_f__Muribaculaceae and Dubosiella showed some correlations with metabolic indicators, inflammation indicators, NAS and occludin. Deletion of the PPARδ gene exacerbated HFD-induced gut microbiota dysbiosis and affected NAFLD through the gut-liver axis.